Allergy education in otolaryngology residency: a survey of program directors and residents. Issue 2 (5th December 2013) - Bailey, Sarah E.; Franzese, Christine; Lin, Sandra Y.
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to survey program directors of the accredited otolaryngology residency programs and resident attendees of the 2013 American Academy of Otolaryngic Allergy (AAOA) Basic/MOC Course regarding resident education and participation as well as assessment of competency in otolaryngic allergy and immunotherapy. Methods A multiple‐choice questionnaire was sent to all accredited otolaryngology residency training programs in the United States as part of resident attendance at the 2013 AAOA CORE Basic/MOC Course. Following this, a similar multiple‐choice survey was sent to all resident attendees from the programs that responded positively. Results Program directors reported that 73% of their academic institutions offer allergy testing and immunotherapy. More PDs than residents indicated that residents participate in allergy practice and perform/interpret skin testing and in vitro testing, and more residents (85%) than program directors (63%) reported inadequate or no allergy training. Program directors and residents equally indicated that residents do not calculate immunotherapy vial formulations or administer immunotherapy injections. The majority of program directors indicated that resident competency in allergy was assessed through direct observation, whereas residents more commonly perceived that no assessment of competency was being performed for any portion of allergy practice. Conclusion This survey demonstrates a discrepancy between program directors and residents regarding resident involvement and adequacy of training in the allergy practice. Although the majority of otolaryngology residencies report offering otolaryngic allergy services and education, the vast majority of residents report inadequate allergy training and less participation in an allergy practice compared to the majority of program directors.